Multilingualism as a Key Challenge for Higher Education Language Policy: The ARQUS Perspective - Bärenfänger, Olaf; Delgado, Alba; Gackle, Kerstin (Verbum, 2022)
Language plays an essential role in education, where it serves as both the medium of instruction and key to communication. To warrant successful teaching, learning, research and academic mobility, universities must develop a clear vision about the role of language(s) at their institution. For example, they must develop strategies to promote continual growth of their students’ and staff’s professional and academic language skills. This article will report on an initiative undertaken within the Arqus European University Alliance to formulate a comprehensive language policy. To do so, five thematic areas essential to language policies in higher education were identified and questions were developed to gather information from all of the partner universities. This information was then incorporated in the planning and design of a language policy for the Alliance. The Arqus Language Policy now stands as a guideline for university members to develop a clear vision of language in higher education as well as a joint reflection and agreement on the role of multilingual communication in society. In the second phase of the project, further actions and measures can be planned on this basis.
Keywords: Language Policy; Higher Education; Higher Education Space; Multilingualism; Pluriculturalism; Language Planning